Microbial art / Suraya Sulaiman ... [et al.] - Sulaiman, Suraya; Wan Ismail, Wan Nordini Hasnor; Othman, Mohd Izani; Mohd Najib, Mohd Nadzri (UiTM Perak Press, 2022)
The term “arts” refers to a wide range of human activities involving cultural involvement, storytelling and creative expression. It includes a variety of media, including photography, installation, decorative arts, printmaking, drawing, and painting. Using cross-disciplinary education to engage students in creative and critical thinking is an excellent way to encourage active learning. By incorporating creative art activities into science lessons, educators can help students develop their attention to detail, skills and creativity while also enhancing their enjoyment and motivation. Students and scientists can use art to express their own cultural and uniqueness into their work experience, creating a higher level of engagement in the successful completion of a project. For example, scientists rely on data visualisation to explain their findings, and using creative design principles to these visualisations can considerably increase their ability to transmit information to readers (Friendly and Denis 2001). Students’ involvement in laboratory settings can also be improved by incorporating multidisciplinary, innovative activities such as painting, creative writing, and music into existing teaching materials.